Cycling of zinc and its isotopes across multiple zones of the Southern Ocean: Insights from the Antarctic Circumnavigation Expedition. (1st January 2020) - Sieber, M.; Conway, T.M.; de Souza, G.F.; Hassler, C.S.; Ellwood, M.J.; Vance, D.
Abstract: Zinc (Zn) is an essential micronutrient, playing an important role in several key processes in marine phytoplankton. Here, we present the first high-resolution depth profiles for dissolved Zn and δ 66 Zn from all major zones of the Southern Ocean, collected during the Antarctic Circumnavigation Expedition in Austral Summer 2016/2017. The dataset reveals that Zn cycling changes between different regions of the Southern Ocean. Within the Antarctic Circumpolar Current (ACC), Zn cycling is closely linked to phosphate (PO4 ), governed by uptake and regeneration, seasonal mixing, and upwelling. Here, uptake by phytoplankton is associated with a very small fractionation (α = 0.99995), resulting in slightly elevated surface δ 66 Zn (up to +0.67‰), overlying a shallow subsurface δ 66 Zn minimum (+0.36‰ at ∼200 m). South of the ACC, a partial coupling of Zn and silicate (Si) results in a shift of the Zn isotope systematics and a deep enrichment of Zn and Si. Two possible mechanisms could potentially cause this change: 1) reversible scavenging onto sinking particulates, or, 2) association of isotopically heavy Zn with diatom frustules. We also observe the effects of regional processes on Zn in the surface Southern Ocean: firstly, natural Fe fertilization near the Balleny Islands appears to lead to reduced Zn uptake (relative to phosphate) by phytoplankton, that is associated with a greater apparent Zn isotope fractionation than elsewhere in the Southern Ocean (α = 0.99987); secondly, meltwater inputs from the Mertz Glacier add small amounts of isotopically light Zn to surface waters near the Antarctic shelf. Overall, we propose that the lack of distinct δ 66 Zn signatures transported in intermediate waters of the lower latitude global oceans is due to near-complete uptake of Zn by phytoplankton in the surface Southern Ocean with only a small isotope fractionation, in contrast to elements like cadmium and silicon.